The Correlation among the Incidences of Sialolithiasis, Urolithiasis, and Cholelithiasis in Samples from the Iraqi Populations - Ali Mihsen Hussein Alyassiri (Medical Journal of Babylon)
Background: There are three types of “stone diseases”: “sialolithiasis (SL), urolithiasis (UL) and cholelithiasis (CL),” which share comorbidities. The risk parameters are present in both spouse and familial profiles. Objective: The study aims to establish a correlation between the types of stone diseases and their familial history. Materials and Methods: The Marjan Teaching Hospital and Al-Hilla Teaching Hospital recorded familial relationships from various registration areas in all hospitals in Babylon province; they also obtained information on stone diseases from all patient records. Babylon-Iraq. The participants (243) had no signs and symptoms of any systemic diseases, and the enrolled participants were assessed for all involved samples without a history of the identified stone disease, Informed consent was obtained from all outpatients or participants. Results: The results of this current study revealed that the incidence of stone diseases was higher in females than in males, with a significant difference (P ˃ 0.001). The age intervals ranged from 18 to 24 years, followed by 33–55 years, and finally 25–32 years. In terms of the incidence of SL, females with family histories exhibited a higher prevalence than males. Conclusion: In terms of the familial incidence of stone pathology, both SL and UL are more common than CL. This study proposed that familial clustering is unique to each stone disease and further indicated that the underlying disease mechanisms are distinct.